In vitro immunostimulation of turbot (Scophthalmus maximus) leucocytes with beta-glucan and/or Photobacterium damsela bacterin - Figueras Huerta, Antonio; Santarém, M. M.; Novoa, Beatriz (Japanese Society of Fish Pathology, 1997)
5 pages, 3 figures Respiratory burst and phagocytic activities of turbot (Scophthalmus maximus) leucocytes were determined after an in vitro incubation of head kidneys with different doses of yeast glucan and Photobacterium damsela (formerly Vibrio damsela) O-antigen. Although there was an increment of these immune functions with the treatment of glucans and O-antigen compared with controls, they were inhibited at high doses (200 μg/ml). The optimum dose of glucan was 50 μg/ml when it was administered alone, but a concentration of 10 μg/ml was enough to produce the stimulatory effect This work was supported by Grant AGF94-1360-CO3-O3 of the Comisión Interministerial de Ciencia y Tecnología (CICYT). María Santarem thanks the Junta Nacional de Investigaçao Científica e Tecnológica (Portugal) for a research fellowship Peer reviewed